Our Experience with 40 Cases of Inferior Vena Cava Interruption - Abascal, Winston; Navarro, Teodoro; Estefan, Alberto; Danza, Rómulo; Praderi, Raúl (Cirugía del Uruguay, 1979)
A series of 40 cases of inferior vena cava interruption is presented. Of them 30 were done with plication and 10 With !igation.